Literacy traps: Society-wide education and individual skill premia - Vidya Atal; Kaushik Basu; John Gray; Travis Lee (Cornell University, Center for Analytical Economics (CAE), 2009)
Using a model of O-ring production function, the paper demonstrates how certain communities can get caught in a low-literacy trap in which each individual finds it not worthwhile investing in higher skills because others are not high-skilled. The model sheds light on educational policy. It is shown that policy for promoting human capital has to take the form of a mechanism for solving the coordination failure in people's choice of educational strategy.
Keywords: D20; I28; J31; 330; education; literacy; O-ring; skill formation; traps; Analphabetismus; Gemeinschaft; Soziale Beziehungen; Bildungsverhalten; Bildungspolitik; Theorie